2005
DOI: 10.1002/pi.1857
|View full text |Cite
|
Sign up to set email alerts
|

Morphology development in polyethylene/polystyrene blends: the influence of processing conditions and interfacial modification

Abstract: The influence of processing conditions and interfacial modification on the morphology evolution and the composition range within which fully co‐continuous high density polyethylene/polystyrene blend structures can exist during blending in a single screw extruder was studied. Blends ranging from pure A to pure B component, with and without compatibilizer, were prepared under two different shear rates. It was found that high shear rates displaced the breakdown–coalescence balance of the dispersed nodules to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Figure 4a shows the morphology of the fractured surface of the binary PE/PS 90/10 blend. The SEM analysis revealed a two-phase morphology with a rather large polydispersity of spherical PS particles in the PE matrix and cavities caused by the removal of nodules as a result of high interfacial tension 4 . The PS domain sizes ranges from 1 to 4 μm in diameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4a shows the morphology of the fractured surface of the binary PE/PS 90/10 blend. The SEM analysis revealed a two-phase morphology with a rather large polydispersity of spherical PS particles in the PE matrix and cavities caused by the removal of nodules as a result of high interfacial tension 4 . The PS domain sizes ranges from 1 to 4 μm in diameter.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work 4 we studied the effect of the processing conditions and interfacial modifi cation on the morphology development in a high density polyethylene/polystyrene blend system. The aim of this contribution is to relate these morphologies to the rheological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Three pieces of each sample were used to obtain an average value. The percent continuity can be defined as the weight ratio of the POE phase involved in the continuous path divided by the total weight of the theoretical POE phase [34]. The POE phase involved in the continuous path is the dissolved phase:…”
Section: Selective Dissolution and Continuity Calculationmentioning
confidence: 99%
“…Jarusuwannapoom et al 45 concluded that DMF is the best solvent since it provided PS fibers with highest productivity and optimal morphological characteristics due to its high boiling point, solution conductivity and high dielectric constant compared to other solvents. Whereas that Casper et al 43 and Jaziri et al 44 used THF to dissolve PS with very good results. As commented above, other solvents were also tested but they did not provided suitable solubility, viscosity, surface tension and/or conductivity to polymeric solutions.…”
Section: Electrospun Heat Management Of Ps and Hips Hybrid Fibersmentioning
confidence: 98%
“…Based on previous studies, [43][44][45][46][47] the best candidates to dissolve the polystyrene (PS) and high-impact polystyrene (HIPS) were DMF and tetrahydrofuran (THF) since both provided appropriate electrospinning properties to the polymer solutions. Jarusuwannapoom et al 45 concluded that DMF is the best solvent since it provided PS fibers with highest productivity and optimal morphological characteristics due to its high boiling point, solution conductivity and high dielectric constant compared to other solvents.…”
Section: Electrospun Heat Management Of Ps and Hips Hybrid Fibersmentioning
confidence: 99%